In search of the self: a positron emission tomography study. - Craik, Fergus I. M.; Moroz, Tara M.; Moscovitch, Morris (Psychological Science., 1999)
A positron emission tomography study was conducted to examine the possibility that encoding of self-related material might activate right frontal areas of the brain. The findings demonstrated that self-related coding yielded left frontal activations similar to those related to other types of semantic coding, but it also yielded specific activations in the right frontal lobe. It is concluded that the concept of self incorporates both general schematic structures and additional specific components involved in episodic memory retrieval.